Law no. 82/2017 amending some provisions of the income tax law promulgated by law no. 91 of the year 2005 = قانون رقم 82 لسنة 2017 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
law no. 82 of the year 2017 amending some provisions of the income tax law promulgated by law no. 91 of the year 2005 قانون رقم 82 لسنة 2017 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005